2009
DOI: 10.1177/1098611109348473
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Workplace Experiences of Police Patrol Officers: The Role of Race, Sex, and Sexual Orientation

Abstract: Reform efforts in many police departments have diversified the workforce, especially with regard to race, sex, and sexual orientation. Research, however, has demonstrated that the assimilation of these officers has not been problem-free. Using data collected from a large, municipal police department, this article examines the workplace experiences of patrol officers and a potential consequence of those experiences: stress. We find that being female and being a racial/ethnic minority brings with it substantiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 46 publications
(55 reference statements)
5
98
1
Order By: Relevance
“…It is also not surprising that the female officers believed that there was more gender bias in the department than the male officers. Again, studies on the work place experiences of women have consistently produced the same finding (Hassell & Brandl, 2009;Morash & Haarr, 1995;National Research Council, 2004).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…It is also not surprising that the female officers believed that there was more gender bias in the department than the male officers. Again, studies on the work place experiences of women have consistently produced the same finding (Hassell & Brandl, 2009;Morash & Haarr, 1995;National Research Council, 2004).…”
Section: Discussionsupporting
confidence: 51%
“…It is not surprising, nevertheless, that female officers perceived their physical stature to be an issue among their male counterparts. Studies have consistently found that women perceive themselves to be underestimated because of their physical size (Hassell & Brandl, 2009;Martin, 1979;Morash & Haarr, 1995). It is also not surprising that the female officers believed that there was more gender bias in the department than the male officers.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…With very few exceptions (Burke, 1993, 1994; Loftus, 2008), scholarship on LGB sexualities within police organisations is largely confined to the US (Leinen, 1993; Belkin and McNichol, 2002; Miller et al ., 2003; Myers et al ., 2004; Lyons et al ., 2008; Colvin, 2009; Hassell and Brandl, 2009). There is a general consensus among scholars that the employment of lesbians and gay men in the police represents a threat to the gendered characteristics of police work, with its emphasis on physical strength, aggression, authority and technical competence.…”
Section: Lgb Identity and Disclosure In Police Organisationsmentioning
confidence: 99%
“…Just as men and women differ, so too might the experiences of racial/ethnic minorities. In other words, Black and Latino officers' experiences may not be uniform (see, for example, Hassell & Brandl, 2009). …”
Section: Introductionmentioning
confidence: 99%